From Obligation to Action: Advancing Victim Assistance and Environmental Remediation at the First Meeting of States Parties to the Treaty on the Prohibition of Nuclear Weapons. Issue 2 (2nd July 2020) - Docherty, Bonnie
ABSTRACT: As entry into force approaches, the time has come to start planning for the First Meeting of States Parties (1MSP) to the Treaty on the Prohibition of Nuclear Weapons (TPNW). Guided by the treaty's goal of eliminating the "catastrophic humanitarian consequences" of nuclear weapons, the 1MSP should address not only the TPNW's provisions to prevent future detonations, but also its positive obligations to respond to the suffering caused by past use and testing. This commentary examines the meeting's role in turning the TPNW's articles on victim assistance, environmental remediation, and international cooperation and assistance into action. It highlights the 1MSP's significance, proposes an effective structure, and examines the substance of its discussions and outcome documents. In all of these areas, the 1MSP can draw on humanitarian disarmament precedent while adapting it to the nuclear weapons context. By making the positive obligations a long-term priority and creating a framework for maximizing their impact, the 1MSP will pave the way for fully realizing the TPNW's humanitarian purpose.